Hans Werner Henze, Ingeborg Bachmann: Der Prinz von Homburg. Operatic adaptation of Kleist’s drama - Beata Kornatowska (Przestrzenie Teorii)
The article aims at showing how complex can be the relationship between literary prototype and operatic work. It analyses the adaptation of Heinrich von Kleist’s drama by two outstanding postwar artists: the Austrian author Ingeborg Bachmann (1926–1973) and the German composer Hans Werner Henze (1926–2012). They not only adjust the dramatic text to the needs of the operatic medium. They also, very much in the spirit of their times (1958), try to rethink, to “save” as they put it, a work of art misused by the ideology of Wilhelminism and the Third Reich. In their interpretation they turn their back on military and political content of the drama, focus their attention on the person of the Prince, glorifying him as a dreamer and outsider.